ASSESSMENT OF NURSES' KNOWLEDGE REGARDING PERSONAL PROTECTIVE EQUIPMENT AT TERTIARY CARE HOSPITAL LAHORE - HUSSAIN , MG; HAMEED , S; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Personal Protective Equipment (PPE) is crucial for protecting healthcare workers from occupational hazards and infections, particularly in high-risk environments such as hospitals. Adequate knowledge and proper use of PPE are essential to ensure the safety of both healthcare workers and patients. This study aimed to assess the knowledge, attitudes, and practices of nurses regarding PPE at a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study design was utilized. A structured questionnaire was used to collect data from 152 nurses working in various departments of the hospital. Purposive sampling was employed, and the sample size was determined using RaoSoft with a 95% confidence interval and a 0.5% margin of error. The questionnaire comprised sections on demographic information, knowledge assessment, and attitudes and practices evaluation. Data were analyzed using SPSS version 25.0, with descriptive statistics and chi-square tests to identify associations between demographic characteristics and knowledge levels. Results: Of the 152 participants, 77% were female, with a mean age of 36.5 years (SD ± 9.05 years). Most participants held a diploma in nursing (46%), and the majority (93.4%) had less than 12 years of professional experience. The findings revealed that 67% of nurses demonstrated good knowledge of PPE, 20% had average knowledge, and 13% exhibited poor knowledge. While 92% of participants reported being knowledgeable about PPE usage, inconsistencies were noted in the adherence to specific practices, such as glove and mask usage. Additionally, only 34% of participants believed that consistent use of PPE would reduce their risk of infection, indicating a potential gap between perceived and actual knowledge. Conclusion: The study highlights both strengths and gaps in nurses' knowledge and practices regarding PPE at a tertiary care hospital in Lahore. While most nurses demonstrated a satisfactory understanding of PPE, inconsistencies in practical application underscore the need for targeted training and reinforcement of guidelines. Regular training sessions, active monitoring, and continuous professional development are essential to enhance adherence to PPE protocols and safeguard healthcare workers in resource-limited settings like Pakistan.